2014
DOI: 10.1021/ie500666m
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensionally Ordered Macroporous MnxCe1–xOδ and Pt/Mn0.5Ce0.5Oδ Catalysts: Synthesis and Catalytic Performance for Soot Oxidation

Abstract: Three-dimensionally ordered macroporous (3DOM) Mn x Ce1–x Oδ oxides with different ratios of Mn to Ce were successfully synthesized by colloidal crystal template (CCT) method, and 3DOM Pt/Mn0.5Ce0.5Oδ with varied Pt loadings were prepared by in situ ethylene glycol (EG) reduction method. 3DOM Mn x Ce1–x Oδ supports exhibited well-defined 3DOM nanostructure, and Pt nanoparticles (NPs) with 1–2 nm size were evenly dispersed on the inner walls of uniform macropores. Among 3DOM Mn x Ce1–x Oδ catalysts, 3DOM Mn0.5C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(34 citation statements)
references
References 55 publications
1
33
0
Order By: Relevance
“…Recent studies have produced a variety of colloid-based porous Ce-Zr binary oxides and composite structures incorporating metal NPs. 339,343,344 For example, Arandiyam et al fabricated 3D ordered macro/mesoporous Pt/Ce 0.6 Zr 0.3 Y 0.1 O 2 (CZY) catalysts for methane combustion using PMMA as hard template and pluronic (P123) as surfactant (Figure 24 A,B). 348 The excellent catalytic activity of Pt/CZY was ascribed to an increase in surface area due to its unique macro/mesoporous structure as well as its high concentration of adsorbed oxygen, good low-temperature reducibility, and strong catalyst-support interaction due to composition.…”
Section: Factors Influencing Cbpm Catalystsmentioning
confidence: 99%
“…Recent studies have produced a variety of colloid-based porous Ce-Zr binary oxides and composite structures incorporating metal NPs. 339,343,344 For example, Arandiyam et al fabricated 3D ordered macro/mesoporous Pt/Ce 0.6 Zr 0.3 Y 0.1 O 2 (CZY) catalysts for methane combustion using PMMA as hard template and pluronic (P123) as surfactant (Figure 24 A,B). 348 The excellent catalytic activity of Pt/CZY was ascribed to an increase in surface area due to its unique macro/mesoporous structure as well as its high concentration of adsorbed oxygen, good low-temperature reducibility, and strong catalyst-support interaction due to composition.…”
Section: Factors Influencing Cbpm Catalystsmentioning
confidence: 99%
“…Interestingly, although the sample H 2 reduction peak temperature for FeCe‐SG is slightly higher than the sample FeCe‐MM, it has the largest H 2 reduction peak area, indicating that the sample consumes the most H 2 . Studies have shown that the reason for the poor selectivity of catalyst N 2 is that NH 3 is excessively oxidized at the active site, and excessive NH participates in the catalytic reaction to form a side reaction product N 2 O . However, FeCe‐SG samples consume more H 2 in this temperature range, and have a higher degree of oxidation, and may over oxidize NH 3 to NH.…”
Section: Resultsmentioning
confidence: 99%
“…50 PM combustion is a typically deep oxidation reaction, the intrinsic redox performance of catalysts plays a major role in PM oxidation. 37 Topsøe 51 proposed a catalytic cycle for the SCR reaction, referring to both acid-base and redox functions. Previous studies by Lietti et al indicated that the NH 3 -SCR catalyst with redox functions dominated the catalytic performance.…”
Section: The Results Of H 2 -Tpr and Nh 3 -Tpdmentioning
confidence: 99%